A method for quantitative imaging of electrical properties of human tissues from only amplitude electromagnetic data. (2nd January 2019) - Bevacqua, Martina T; Bellizzi, Gennaro G; Crocco, Lorenzo; Isernia, Tommaso
Abstract: The estimation of electrical properties of living biological tissues is relevant to several medical applications ranging from hyperthermia treatment planning to dosimetry and, more in general, is pivotal for a fundamental understanding of bioelectromagnetic interactions. Non-invasive electromagnetic imaging, either based on the processing of electric fields measured via microwave tomography or magnetic fields acquired in magnetic resonance is suitable to pursue this goal. In this framework, the possibility of imaging without the need of phase information would be extremely relevant, as it would enable simpler and more reliable devices and would avoid limiting assumptions typically used in the literature. With reference to the canonical yet significant 2D case, in this paper we propose an inverse scattering approach for tissue characterization from only-amplitude electromagnetic data, which, by virtue of a unified mathematical framework, is viable for both microwave tomography and magnetic resonance imaging. The key feature of the method is the innovative use of morphological maps derived by other medical imaging modalities as prior spatial information. In particular, these images are exploited to define a convenient and effective patient-specific representation of the unknowns. The approach is tested against simulated data derived from anatomically realistic scenarios.